Preparation and characterization of MOCVD thin films of indium tin oxide - Akinwunmi, O.O; Eleruja, Marcus Adebola; Olowolafe, J.O; Adegboyega, G.A (Optical Materials, 2023)
International journal Optical Materials Vol13,No2,p.255-259